Lower anterior cingulate volume in seriously violent men with antisocial personality disorder or schizophrenia and a history of childhood abuse. (February 2014) - Kumari, Veena; Uddin, Shahir; Premkumar, Preethi; Young, Susan; Gudjonsson, Gisli H; Raghuvanshi, Satya; Barkataki, Ian; Sumich, Alexander; Taylor, Pamela; Das, Mrigendra
Objective: Antisocial personality disorder (ASPD) and schizophrenia, as well as childhood abuse, are associated with violent behaviour and show marked volumetric reduction in the anterior cingulate (AC), a brain region implicated in regulation of violence through its involvement in decision making, empathy, impulse control, and emotion regulation. The present study examined, for the first time to the authors' knowledge, the grey matter volume of the AC in relation to seriously violent behaviour and childhood psychosocial deprivation (including physical and sexual abuse) in the context of a mental disorder (schizophrenia or ASPD). Methods: Fifty-seven men [14 with ASPD and a history of serious violence; 13 with schizophrenia and a history of serious violence (VSZ); 15 with schizophrenia without a violence history (SZ); 15 nonviolent healthy participants] underwent whole-brain magnetic resonance imaging and were rated on the presence of physical abuse, sexual abuse, neglect, extreme poverty, foster home placement, criminal parent, severe family conflict, and broken home (collectively 'psychosocial deprivation'). Stereological volumetric ratings of the AC were examined for group differences and their association with childhood psychosocial deprivation. Results: A higher proportion of ASPD and VSZ patients had suffered psychosocial deprivation as children, in particular severe physical abuse, relative to SZ patients and healthy participants. ASPD and VSZ, but not SZ, patients had significantly lower AC volume relative to healthy participants. AC volumes correlated negatively with (total) psychosocial deprivation as well as physical and sexual abuse ratings. Group differences in AC volume became nonsignificant when psychosocial deprivation ratings were covaried for. Conclusions: Violent mentally disordered individuals with ASPD or schizophrenia suffer from a significant AC volume loss and this deficit, at least in part, is explained by their histories of stressful childhood experiences. Current and future therapies aiming to reduce violence in such populations would benefit by attending to biological (and other) correlates of childhood abuse.